Analisis Tingkat Kemiskinan Kaum Urban Berdasarkan Indeks Cibest di Kecamatan Kepil Kabupaten Wonosobo - Nur Imam Saifuloh (Institut Agama Islam Negeri Madura, 2018)
Inequality of economy system in Indonesia impacts to the poverty in rural area is high. This condition makes people in rural move to urban as called as urbanization. By using CIBEST Index, this study aim to describe the poverty in Kepil District and analyze is there a differences among village based on urbanization rate. Type of study had been used in this research is quantitative descriptive by study case approach. Questionare, interview and documentation are instrument research that used to collect data. And to analyze it, use CIBEST Index and SPSS software with function of Cross-Tabulation. The result of this study descibe the urban poverty in Kepil District dominated by population in second quadrant, it is 112 family (91,1%) of total population. While the other family is in prosperous condition (first quadrant), it only 11 family (8,9%). Value of Welfare (W) on CIBEST Index is 0,089 and the Material Poverty (MP) as the second quadrant is 0,91. There is not difference among the village based on urbanization rate. It known from Asymptotic Significance value is bigger than probability value (0,055 > 0,05).